Variation of the Bulk Etch Rate of Nuclear Track Detector CR-39 With the Chemical Etchant Solution Normality - Ahmed A. Al-obedy; Ammar A. AL-Battawy; Omar K. Younus (Tikrit Journal of Pure Science)
The variation of the bulk etch rate (VB) of nuclear track detector CR-39 with the normality of the chemical etchant were studied. The removal thickness measurement method is used to determine the bulk etch rate. the detectors were etched by an aqueous solution of  NaOH with normalities (4, 5, 6, 7) N at temperature (70±1) oC. It was found that the bulk etch rate is exponentially increasing with the normality of the solution and its values are (0.687, 1.421, 0.954, 2.082) µm/h at normalities (4, 5, 6, 7) N respectively. the relation between the bulk etch rate and the etchant normality was an exponential relation and the results showed good agreement with the results of the others used other normalities and another measurement method.